Letter to the editor - Bertolaccini, Luca (BioMed Central, 2010)
A response to Dango S, Lin R, Hennings E, Passlick B. Initial experience with a synthetic sealant PleuraSeal™ after pulmonary resections: a prospective study with retrospective case matched controls. Journal of Cardiothoracic Surgery 2010, 5:50.